Modulation of defect-mediated energy transfer from ZnO nanoparticles for the photocatalytic degradation of bilirubin - Bora, Tanujjal; Lakshman, Karthik Kunjali; Sarkar, Soumik; Makhal, Abhinandan; Sardar, Samim; Pal, Samir Kumar; Dutta, Joydeep (Beilstein Journal of Nanotechnology, 2013)
In recent years, nanotechnology has gained significant interest for applications in the medical field. In this regard, a utilization of the ZnO nanoparticles for the efficient degradation of bilirubin (BR) through photocatalysis was explored. BR is a water insoluble byproduct of the heme catabolism that can cause jaundice when its excretion is impaired. The photocatalytic degradation of BR activated by ZnO nanoparticles through a non-radiative energy transfer pathway can be influenced by the surface defect-states (mainly the oxygen vacancies) of the catalyst nanoparticles. These were modulated by applying a simple annealing in an oxygen-rich atmosphere. The mechanism of the energy transfer process between the ZnO nanoparticles and the BR molecules adsorbed at the surface was studied by using steady-state and picosecond-resolved fluorescence spectroscopy. A correlation of photocatalytic degradation and time-correlated single photon counting studies revealed that the defect-engineered ZnO nanoparticles that were obtained through post-annealing treatments led to an efficient decomposition of BR molecules that was enabled by Förster resonance energy transfer.
Keywords: bilirubin; Förster resonance energy transfer (FRET); neonatal jaundice; oxygen vacancy; photocatalysis; phototherapy; zinc oxide nanoparticles

(untitled) - London, I. M.; West, R.; Shemin, D.; Rittenberg, D. (J. Biol. Chem., 1950)

(untitled) - Maisels, M. J.; McDonagh, A. F. (N. Engl. J. Med., 2008)

(untitled) - Robertson, S. E.; Hull, B. P.; Tomori, O.; Bele, O.; LeDuc, J. W.; Esteves, K. (JAMA, J. Am. Med. Assoc., 1996)

(untitled) - Vreman, H. J.; Wong, R. J.; Stevenson, D. K. (Semin. Perinatol., 2004)

(untitled) - Stocker, R.; Glazer, A. N.; Ames, B. N. (Proc. Natl. Acad. Sci. U. S. A., 1987)

(untitled) - Paciotti, G. F.; Myer, L.; Weinreich, D.; Goia, D.; Pavel, N.; McLaughlin, R. E.; Tamarkin, L. (Drug Delivery, 2004)

(untitled) - Wu, X.; Liu, H.; Liu, J.; Haley, K. N.; Treadway, J. A.; Larson, J. P.; Ge, N.; Peale, F.; Bruchez, M. P. (Nat. Biotechnol., 2002)

(untitled) - Hirsch, L. R.; Stafford, R. J.; Bankson, J. A.; Sershen, S. R.; Rivera, B.; Rrice, R. E.; Hazle, J. D.; Halas, N. J.; West, J. L. (Proc. Natl. Acad. Sci. U. S. A., 2011)

(untitled) - Zhou, J.; Xu, N. S.; Wang, Z. L. (Adv. Mater., 2006)

(untitled) - Baruah, S.; Rafique, R. F.; Dutta, J. (NANO, 2008)

(untitled) - Baruah, S.; Sinha, S. S.; Ghosh, B.; Pal, S. K.; Raychaudhuri, A. K.; Dutta, J. (J. Appl. Phys., 2009)

(untitled) - Hofmann, D. M.; Pfisterer, D.; Sann, J.; Meyer, B. K.; Tena-Zaera, R.; Munoz-Sanjose, V.; Frank, T.; Pensl, G. (Appl. Phys. A: Mater. Sci. Process., 2007)

(untitled) - Vanheusden, K.; Seager, C. H.; Warren, W. L.; Tallant, D. R.; Voigt, J. A. (Appl. Phys. Lett., 1996)

(untitled) - Van Dijken, A.; Meulenkamp, E. A.; Vanmaekelbergh, D.; Meijerink, A. (J. Phys. Chem. B, 2000)

(untitled) - Sarkar, S.; Makhal, A.; Baruah, S.; Mahmood, M. A.; Dutta, J.; Pal, S. K. (J. Phys. Chem. C, 2012)

(untitled) - Chen, Z. Q.; Yamamoto, S.; Maekawa, M.; Kawasuso, A.; Yuan, X. L.; Sekiguchi, T. (J. Appl. Phys., 2003)

(untitled) - Xu, J.-P.; Shi, S.-B.; Li, L.; Zhang, X.-S.; Wang, Y.-X.; Chen, X.-M. (Chin. Phys. Lett., 2010)

(untitled) - Lin, B.; Fu, Z.; Jia, Y.; Liao, G. (J. Electrochem. Soc., 2001)

(untitled) - Sanyal, D.; Roy, T. K.; Chakrabarti, M.; Dechoudhury, S.; Bhowmick, D.; Chakrabarti, A. (J. Phys.: Condens. Matter, 2008)

(untitled) - Zhang, Y.; Fa, W.; Yang, F.; Zheng, Z.; Zhang, P. (Ionics, 2010)

(untitled) - Fan, H. B.; Yang, S. Y.; Zhang, P. F.; Wei, H. Y.; Liu, X. L.; Jiao, C. M.; Zhu, Q. S.; Chen, Y. H.; Wang, Z. G. (Chin. Phys. Lett., 2007)

(untitled) - Mtangi, W.; Auret, F. D.; Diale, M.; Meyer, W. E.; Chawanda, A.; De Meyer, H.; Janse Van Rensburg, P. J.; Nel, J. M. (J. Appl. Phys., 2012)

(untitled) - Yang, Z.; Zhang, C. (J. Mol. Catal. A: Chem., 2009)

(untitled) - Yang, Z.-p.; Yan, J.-l.; Zhang, C.-j.; Luo, S.-q. (Colloids Surf., B, 2011)

(untitled) - Irimpan, L.; Ambika, D.; Kumar, V.; Nampoori, V. P. N.; Radhakrishnan, P. (J. Appl. Phys., 2008)

(untitled) - Scardi, P.; Leoni, M.; Delhez, R. (J. Appl. Crystallogr., 2004)

(untitled) - Ye, J. D.; Gu, S. L.; Qin, F.; Zhu, S. M.; Liu, S. M.; Zhou, X.; Liu, W.; Hu, L. Q.; Zhang, R.; Shi, Y.; Zheng, Y. D. (Appl. Phys. A: Mater. Sci. Process., 2005)

(untitled) - Van Dijken, A.; Meulenkamp, E. A.; Vanmaekelbergh, D.; Meijerink, A. (J. Lumin., 2000)

(untitled) - Vanheusden, K.; Warren, W. L.; Seager, C. H.; Tallant, D. R.; Voigt, J. A.; Gnade, B. E. (J. Appl. Phys., 1996)

(untitled) - Wei, S.; Lian, J.; Wu, H. (Mater. Charact., 2010)

(untitled) - Sleiman, M.; Vildozo, D.; Ferronato, C.; Chovelon, J.-M. (Appl. Catal., B: Environ., 2007)

Principles of Fluorescence Spectroscopy - Lakowicz, J. R. (Springer Science+Business Media, LLC, 1999)